NURSING PROVISION IN PSYCHOLOGICAL ASPECT MANAGEMENT OF NATURAL DISASTER - Munandar, Arif; Wardaningsih, Shanti (Jurnal Keperawatan, 2018)
Natural disasters are an event or series of events caused by natural phenomena such as earthquakes, tsunamis, volcanoes, floods, droughts, hurricanes and landslides, resulting in human casualties, environmental damage, property losses objects, and psychological effects. Therefore, the need for nurse preparedness is especially special on the psychological aspect aside from the physical aspect. Nurse personnel is the first milestone that will be sought by the people affected by disaster, because nurses as the front line in a health service has a responsibility and a big role in handling the patient's daily emergency and disaster strikes. To know nurse preparedness in psychological aspect in facing natural disaster. The writing of this journal uses a literature study approach from several sources selected based on the criteria set by the author. The research journal was obtained from several databases, namely PubMed and BioMedCentral (BMC) Psychiatry. In total, the literature review consists of 10 journals, 4 studies report effective outcomes including knowledge, skills, self-awareness, interest, intellectual, cooperation, and motivation need to be prepared to support disaster management, 5 research reports that nurses need to prepare themselves on the psychological aspect in the form of cognitive, intellectual, interest, attitude, clinical skills education and rescue comprehension with basic principles of psychosocial support. Last 1 study reported the result that the need for training for administrators on hospital management in disaster preparedness. The psychological aspect is very important that must be prepared by the nurse in facing natural disaster, thus preventing the occurrence of psychological impact (in the form of psychological disorders such as depression, anxiety and other mental disorders) either self-nurse or victim to be handled by natural disaster happen.